A new species of the genus Blaptogonia from the Himalayas with four DNA markers (Coleoptera, Tenebrionidae, Blaptini) - Xiu-Min Li; Xing-Long Bai; Guo-Dong Ren (ZooKeys, 2018)
A new species of the genus Blaptogonia Medvedev, 1998, B. zhentanga sp. n., is described from the southern Himalayas of China. Two fragments of mitochondrial protein-coding genes (COI, Cytb), one fragment of mitochondrial ribosomal RNA gene (16S), and one fragment of nuclear rRNA gene (28SD2) of the new species were obtained. A key to the known species of the genus is presented.